2008
DOI: 10.1515/jbcpp.2008.19.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phytochemical and biological property analysis to detect the genuineness of substitutes of the plant Moovila in drug preparations

Abstract: Pseudarthria viscida is the preferred source of the raw drug Salaparni in Ayurvedic system of medicine, especially in the preparation of Dasamoolarishtam. Due to its scarcity, other trifoliate leguminous plants, particularly the species of Desmodium and Uraria are used as substitutes. The phytochemical and biological properties of these plants were analyzed to sort out the genuineness of the substitutes. Qualitative as well as quantitative chemical profiles obtained for P. viscida showed similarity to U. rufes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As it effectively arrests bleeding and alleviates edema, it is a valuable panacea for heart diseases and blood disorders (Rajendran et al 2007). Other properties like antihypertensive (Klaus et al 1995), antioxidant (Mathew and Sasikumar 2007;Vijayabaskaran et al 2010a), antiulcer (Babu et al 2008), antifungal (Deepa et al 2004), antidiarrheal (Rajendran et al 2007;Vijayabaskaran et al 2010b) and antitumor (Vijayabaskaran et al 2007;Rajendran et al 2010) have also been reported from P. viscida.…”
Section: Introductionmentioning
confidence: 96%
“…As it effectively arrests bleeding and alleviates edema, it is a valuable panacea for heart diseases and blood disorders (Rajendran et al 2007). Other properties like antihypertensive (Klaus et al 1995), antioxidant (Mathew and Sasikumar 2007;Vijayabaskaran et al 2010a), antiulcer (Babu et al 2008), antifungal (Deepa et al 2004), antidiarrheal (Rajendran et al 2007;Vijayabaskaran et al 2010b) and antitumor (Vijayabaskaran et al 2007;Rajendran et al 2010) have also been reported from P. viscida.…”
Section: Introductionmentioning
confidence: 96%
“…It is used to treat vitiated conditions of pita and vata, asthma, tuberculosis, helminthiasis, dyspepsia, diarrheas, neurasthenia, diabetes, cardiopathy, hyperthermia and general debility and as a nasal drop in headache. The ethanol-induced gastric ulceration in mice was significantly reduced by oral administration of P. viscida extract [226]. …”
Section: Introductionmentioning
confidence: 99%